2017
DOI: 10.1097/itx.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Mrgprs activation is required for chronic itch conditions in mice

Abstract: Introduction Chronic itch has been drawing much attention due to its clinical significance and the complexity of its mechanisms. To facilitate the development of anti-itch strategies, it is necessary to investigate the key players in itch sensation under chronic itch conditions. Several members of the Mrgpr family were identified as itch receptors that detect cutaneous pruritogens in primary sensory neurons. However, the role of Mrgprs in chronic itch conditions has not been well described. Methods Scratchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…The complete overlap of S1P-273 responsive neurons with TRPV1 + neurons is consistent with a role for S1P in itch and pain. Previous 274 studies have shown that the MrgprA3+ subpopulation of TRPA1 + neurons is required for many forms of Zhu et al, 2017). In keeping with our hypothesized role for S1P in itch, 80% of 277 chloroquine-responsive MrgprA3 + neurons responded to S1P (Fig.…”
supporting
confidence: 76%
“…The complete overlap of S1P-273 responsive neurons with TRPV1 + neurons is consistent with a role for S1P in itch and pain. Previous 274 studies have shown that the MrgprA3+ subpopulation of TRPA1 + neurons is required for many forms of Zhu et al, 2017). In keeping with our hypothesized role for S1P in itch, 80% of 277 chloroquine-responsive MrgprA3 + neurons responded to S1P (Fig.…”
supporting
confidence: 76%
“…Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid associated with a variety of skin disorders, including psoriasis (Checa et al, 2015;Myśliwiec et al, 2016), atopic/allergic contact dermatitis (Kohno et al, 2004;Sugita et al, 2010), and scleroderma (Castelino and Varga, 2014), as well as neuropathic pain (Patti et al, 2012;Janes et al, 2014) and other inflammatory diseases (Rivera et al, 2008;Chiba et al, 2010;Tränkner et al, 2014;Donoviel et al, 2015;Roviezzo et al, 2015). S1P signaling via S1P receptor 1 (S1PR1) facilitates the migration, recruitment, and activation of immune cells (Matloubian et al, 2004;Cyster and Schwab, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence supporting both protective and pathogenic effects of S1P signaling in mouse and human chronic itch and inflammatory diseases. In humans, elevated serum S1P is correlated with disease severity in both psoriasis and systemic sclerosis (Castelino and Varga, 2014;Checa et al, 2015;Thieme et al, 2017). Furthermore, ponesimod, an S1PR modulator and blocker of S1P signaling, appears to be promising for psoriasis treatment in humans (Brossard et al, 2013;Vaclavkova et al, 2014;Krause et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ample evidence has demonstrated that nerve injury and inflammation can induce dysregulation of ion channel expression, which results in enhanced neuronal excitability that underlies chronic neuropathic and inflammatory pain (Waxman and Zamponi, 2014). This notion is further supported by the morphological and physiological changes of itch-sensing neurons under chronic itch conditions (Akiyama et al, 2010;Qu et al, 2014;Valtcheva et al, 2015;Zhu et al, 2017). For example, our recent studies demonstrated that NP2 MrgprA3 + neurons exhibit elevated itch receptor expression and hyperinnervation in the skin in a mouse dry skin model (Zhu et al, 2017) and enhanced excitability and spontaneous activities in a contact dermatitis model (Qu et al, 2014).…”
Section: Introductionmentioning
confidence: 95%